"Schizophrenic" self-assembly of dual thermoresponsive block copolymers bearing a zwitterionic and a non-ionic hydrophilic block. (28th July 2017) - Hildebrand, Viet; Heydenreich, Matthias; Laschewsky, André; Möller, Heiko M.; Müller-Buschbaum, Peter; Papadakis, Christine M.; Schanzenbach, Dirk; Wischerhoff, Erik
Abstract: Several series of presumed dual thermo-responsive diblock copolymers consisting of one non-ionic and one zwitterionic block were synthesized via consecutive reversible addition-fragmentation chain transfer (RAFT) polymerization. For all copolymers, poly(N-isopropylmethacrylamide) was chosen as non-ionic block that shows a coil-to-globule collapse transition of the lower critical solution temperature (LCST) type. In contrast, the chemical structure of zwitterionic blocks, which all belonged to the class of poly(sulfobetaine methacrylate)s, was varied broadly, in order to tune their coil-to-globule collapse transition of the upper critical solution temperature (UCST) type. All polymers were labeled with a solvatochromic fluorescent end-group. The dual thermo-responsive behavior and the resulting multifarious temperature-dependent self-assembly in aqueous solution were mapped by temperature-resolved turbidimetry, 1 H NMR spectroscopy, dynamic light scattering (DLS), and fluorescence spectroscopy. Depending on the relative positions between the UCST-type and LCST-type transition temperatures, as well as on the width of the window in-between, all the four possible modes of stimulus-induced micellization can be realized. This includes classical induced micellization due to a transition from a double hydrophilic, or respectively, from a double hydrophobic to an amphiphilic state, as well as "schizophrenic" behavior, where the core- and shell-forming blocks are inverted. The exchange of the roles of the hydrophilic and hydrophobic block in the amphiphilic states is possible through a homogeneous intermediate state or a heterogeneous one. Graphical abstract: Highlights: Well-defined zwitterionic block copolymers are made by RAFT polymerization. The copolymers show dual thermo-responsive behavior in aqueous solution. The individual polymer blocks show separate UCST and LCST-transitions. Temperature dependent 1 H NMR, dynamical light scattering and fluorescence studies. Schizophrenic micellization behavior by inversion of core- and shell-forming blocks.